A Prospective Study of Platelet-Rich Plasma as Biological Augmentation for Acute Achilles Tendon Rupture Repair. (28th December 2016) - Zou, Jian; Mo, Xiaolian; Shi, Zhongmin; Li, Tanzhu; Xue, Jianfeng; Mei, Guohua; Li, Xiaolin
Abstract : Acute Achilles tendon rupture is one of the most common tendon injuries in adults. We hypothesized that Platelet-Rich Plasma (PRP) can be used as biological augmentation for surgical treatment of acute Achilles tendon rupture. Our study is a prospective randomized controlled trial. Patients with acute Achilles tendon rupture undergoing surgical repair were randomly assigned into either control group or PRP group. End-to-end modified Krackow suture was performed in both groups. In the PRP group, PRP was injected into the paratenon sheath and around the ruptured tissue after the tendon was repaired. Postoperatively we evaluated isokinetic muscle strength at 3, 6, 12, and 24 months. In addition, ankle ROM, calf circumference, Leppilahti score, and the SF-36 score were evaluated at 6, 12, and 24 months after operation. At 3 months, the PRP group had better isokinetic muscle. The PRP group also achieved higher SF-36 and Leppilahti scores at 6 and 12 months. At 24 months, the PRP group had an improved ankle range of motion compared to the control group. Our study results suggest that PRP can serve as a biological augmentation to acute Achilles tendon rupture repair and improves both short and midterm functional outcomes.